Mayfly taxonomy (Arthropoda: Hexapoda: Ephemeroptera) during the first two decades of the twenty-first century and the concentration of taxonomic publishing - Jacobus, Luke M.; Salles, Frederico F.; Price, Ben; Pereira-Da-Conceicoa, Lyndall; Dominguez, Eduardo; Suter, P.j.; Molineri, Carlos; Tiunova, Tatyana M.; Sartori, M. (Zootaxa, 2021)
The twentieth anniversary of the first issue of Zootaxa (De Moraes & Freire, 2001) provides an appropriate opportunity to reflect on some trends in global Ephemeroptera taxonomy publishing over the last two decades, with a focus on the description of new species and the outsized role of the journals Zootaxa and ZooKeys, in particular. Detailed reviews of world Ephemeroptera knowledge up to about 2000 were collected in a series of nine papers from a symposium on the subject, published together in the proceedings of the ninth International Conference on Ephemeroptera (Domínguez 2001). Domínguez & Dos Santos (2014) provided updates and analysis for South America up to the year 2012. More recent detailed accounts of regional and taxonomic diversity, and other aspects of mayfly biology and ecology, were reviewed by Jacobus et al. (2019), while Ogden et al. (2019) discussed current issues involving higher classification.